Automotive engine metrology - Ali, Salah H. R. (Pan Stanford Publishing, 2017)
"In recent decades, metrology--an accurate and precise technology of high quality for automotive engines--has garnered a great deal of scientific interest due to its unique advanced soft engineering techniques in design and diagnostics. Used in a variety of scientific applications, these techniques are now widely regarded as safer, more efficient, and more effective than traditional ones. This book compiles and details the cutting-edge research in science and engineering from the Egyptian Metrology Institute (National Institute for Standards) that is revolutionizing advanced dimensional techniques through the development of coordinate and surface metrology."--Provided by publisher.